Outcomes of the toxic hepatites caused by alcohol surrogates - I. Yu. Pirogova; I. Yu. Ponomareva; S. P. Sinitsyn; Ye. P. Samokhina; A. S. Gorbunova; Ye. Yu. Startseva; V. S. Chulkov; T. F. Kondrat'yeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate outcomes of toxic hepatites (TH) after intake of alcohol surrogates («Mozhzhevelovy» spirit for external use) with development of original prognostic model of patients survival.Material and methods. Retrospective analysis of clinical and laboratory data and survival rates of 80 patients (men 54, women 26, age 32 to 49 years), admitted to the hospital in 2006–2007, with evaluation of outcomes in 2012 was carried out. Statistical analysis of the data was carried out by Statistica-6 and Medcalc (using logistical regression and ROC-curves plotting) software packages. For evaluation of the disease prognosis MELD index and Hy's Law were determined, as well as R ratio (ratio of hepatocellular and-or cholestatic lesions).Results. All patients had clinical signs of severe TH with prominent treatment-resistant cholestatic syndrome. Within the first month of disease 16 (20%) patients died of liver failure, during following period – 13 patients (19%). Calculation of MELD index and Hy's Law showed their low informative value at this group of patients, R index in 78% of cases indicated mixed lesion and did not affect prognosis. Original prognostic model of survival rate of patients was: blood leukocyte count (OR 4,8, 95%-CI 1,12— 20,55; р=0,03) and creatinine (OR 1,1, 95% CI 0,99– 1,22; р=0,09), prognostic value of the model was 93,3%. Level of direct bilirubin (AUROC 0,79; CI 0,58–0,83) and WBC (AUROC 0,93; CI 0,83-0,98) were prognostically significant.Conclusions. According to authors’ model, the most significant predictors of lethal outcome at TH were severity of inflammatory response, hyperbilirubinemia and hepatorenal syndrome.